2011
DOI: 10.1152/ajprenal.00725.2010
|View full text |Cite
|
Sign up to set email alerts
|

Dystroglycan does not contribute significantly to kidney development or function, in health or after injury

Abstract: Dystroglycan (DG or DAG1) is considered a critical link between the basement membrane and the cytoskeleton in multiple tissues. DG consists of two subunits, an extracellular α-subunit that binds laminin and other basement membrane components, and a transmembrane β-subunit. DG-null mouse embryos die during early embryogenesis because DG is required for Reichert's membrane formation. DG also forms an integral part of the dystrophin-glycoprotein complex in muscle. Although no human DG mutations have been reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 57 publications
0
25
0
2
Order By: Relevance
“…The importance of an intact GBM-integrin-actin axis is illustrated by glomerular diseases in mice with podocyte-specific genetic ablation of Itga3 (2), Itgb1 (3,4), and integrin-linked kinase (5,6) as well as Pierson syndrome and focal segmental glomerulosclerosis in humans, which are caused by mutations in laminin-521 and α-actinin 4, respectively (7,8). In contrast, the contribution of dystroglycan to podocyte adhesion seems minor, as podocyte-specific Dag1-knockout mice do not display glomerular pathology or aggravate the renal phenotype of Itga3-null animals (9). Mice deficient for the tetraspanin Cd151 develop kidney abnormalities similar to, albeit less severe than, those of mice with podocyte-specific Itga3 knockout (2,10).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of an intact GBM-integrin-actin axis is illustrated by glomerular diseases in mice with podocyte-specific genetic ablation of Itga3 (2), Itgb1 (3,4), and integrin-linked kinase (5,6) as well as Pierson syndrome and focal segmental glomerulosclerosis in humans, which are caused by mutations in laminin-521 and α-actinin 4, respectively (7,8). In contrast, the contribution of dystroglycan to podocyte adhesion seems minor, as podocyte-specific Dag1-knockout mice do not display glomerular pathology or aggravate the renal phenotype of Itga3-null animals (9). Mice deficient for the tetraspanin Cd151 develop kidney abnormalities similar to, albeit less severe than, those of mice with podocyte-specific Itga3 knockout (2,10).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that deletion of Cd151, a member of the tetraspanin family, weakens the interaction of ␣3␤1 with laminin in the GBM and leads to a progressive glomerulopathy (5,75). Deletion of dystroglycans specifically from podocytes produces no obvious abnormalities (34). Very little is known about the changes in expression and distribution of integrins or dystroglycans in effaced foot processes compared with intact foot processes.…”
Section: Fpementioning
confidence: 99%
“…Thus dystroglycan can constitutively link up with all three cytoskeletal systems. Despite this repertoire of interactions, dystroglycan is important as a basement membrane link for some (e.g., Reichert's membrane, skeletal muscle, brain cortex, Schwann cell nodes of Ranvier) but not all (e.g., kidney) tissues ( Jarad, Pippin, Shankland, Kreidberg, & Miner, 2011;Moore et al, 2002;Occhi et al, 2005;Saito et al, 2003;Williamson et al, 1997).…”
Section: Laminin Lg Domain Binding To Cell Surface Receptors and Signmentioning
confidence: 99%